Migrasi dan Identitas: Perantau Buton yang Kembali ke Buton Setelah Konflik Maluku 1999–2002 - Blair Palmer (Antropologi Indonesia, 2004)
People from Buton, Southeast Sulawesi, have for centuries migrated to Ambon for work, there forming one of the most prominent communities of 'pendatang' along with the Bugis. Since the beginning of the recent conflicts in Maluku, official figures indicate that over 160,000people have returned to Buton (previous population 450,000) as refugees. This paper discusses the identity of these refugees and how the term 'refugee' may be misleading. Some of the 'refugees', who often ask to be referred to as 'returned migrants', had retained strong connections with their villages in Buton while they were living in Ambon. Their integration back into Butonese society after their flight from the conflict in Ambon poses, however, a number of serious challenges, especially for those born in Ambon. Having always been called 'Butonese' in Ambon, the returned migrants are often referred to as 'Ambonese' after their return to Buton and they often find it hard to adjust to life in Buton. This paper is based on fieldwork currently being undertaken in the village of Boneoge, Buton. I will discuss some aspects of the lives of the returned migrants in Buton, including their interactions with other Butonese people, as well as some of their perspectives on their own experiences. In Buton; perspectives on their identity are thus being expressed and contested through issues such as use of local languages, dance parties, and contested land rights. Their memories of life in Ambon, and of the conflict, also play a role in their constructions of identity, and in how they respond to challenges intheir lives in Buton now. Here memory is seen as a constructive process, which is culturally influenced, structured by narratives, and adapted to a context.